IoT-Enabled Smart Fence: Remote Security and Monitoring Using NodeMCU ESP32 and Blynk - Fadhilah Putri Syahrani; Hadi Kurnia Saputra; Sartika Anori; Winda Agustiarmi; Firas Tayseer Ayasrah; Pham Van Thanh (Journal of Hypermedia & Technology-Enhanced Learning, 2025)
The Internet of Things (IoT) has transformed home security by enabling automated remote monitoring and control systems. This study presents an IoT-enabled smart fence prototype that utilizes the NodeMCU ESP32 microcontroller and the Blynk application to provide secure, efficient remote gate operations. The system allows users to remotely open, close, and lock gates via mobile devices, addressing the limitations of traditional manual methods. Core components include ultrasonic sensors for real-time obstacle detection, relays, and motors, all integrated into a robust hardware-software framework. Testing revealed consistent system responses within two seconds under stable network conditions, with accurate obstacle detection ensuring the safety zone is maintained. Despite network stability challenges, the system is practical, user-friendly, and scalable for residential security applications. Future improvements could incorporate dual connectivity options to enhance network resilience and advanced sensor calibration to improve reliability across varied environments. This cost-effective prototype demonstrates significant potential for modern smart home security applications and future advancements.